Psychometric validation for a brand-new tool for the assessment of executive functions using 360° technology - Francesca Borgnis; Francesca Borghesi; Federica Rossetto; Elisa Pedroli; Mario Meloni; Giuseppe Riva; Francesca Baglio; Pietro Cipresso (Scientific Reports, 2023)
Abstract EXecutive-functions Innovative Tool 360° (EXIT 360°) is an original 360° instrument for an ecologically valid and multicomponent evaluation of executive functioning. This work aimed to test the diagnostic efficacy of EXIT 360° in distinguishing executive functioning between healthy controls (HC) and patients with Parkinson’s Disease (PwPD), a neurodegenerative disease in which executive dysfunction is the best-defined cognitive impairment in the early stage. 36 PwPD and 44 HC underwent a one-session evaluation that involved (1) neuropsychological evaluation of executive functionality using traditional paper-and-pencil tests, (2) EXIT 360° session and (3) usability assessment. Our findings revealed that PwPD made significantly more errors in completing EXIT 360° and took longer to conclude the test. A significant correlation appeared between neuropsychological tests and EXIT 360° scores, supporting a good convergent validity. Classification analysis indicated the potential of the EXIT 360° for distinguishing between PwPD and HC in terms of executive functioning. Moreover, indices from EXIT 360° showed higher diagnostic accuracy in predicting PD group membership compared to traditional neuropsychological tests. Interestingly, EXIT 360° performance was not affected by technological usability issues. Overall, this study offers evidence that EXIT 360° can be considered an ecological tool highly sensitive to detect subtle executive deficits in PwPD since the initial phases of the disease.